A simple completion of Fisher's fundamental theorem of natural selection. Issue 2 (27th December 2020) - Grafen, Alan
Abstract: Fisher's fundamental theorem of natural selection shows that the part of the rate of change of mean fitness that is due to natural selection equals the additive genetic variance in fitness. Fisher embedded this result in a model of total fitness, adding terms for deterioration of the environment and density dependence. Here, a quantitative genetic version of this neglected model is derived that relaxes its assumptions that the additive genetic variance in fitness and the rate of deterioration of the environment do not change over time, allows population size to vary, and includes an input of mutational variance. The resulting formula for total rate of change in mean fitness contains two terms more than Fisher's original, representing the effects of stabilizing selection, on the one hand, and of mutational variance, on the other, making clear for the first time that the fundamental theorem deals only with natural selection that is directional (as opposed to stabilizing) on the underlying traits. In this model, the total (rather than just the additive) genetic variance increases mean fitness. The unstructured population allows an explanation of Fisher's concept of fitness as simply birth rate minus mortality rate, and building up to the definition in structured populations. Abstract : Fisher's model of the total change in mean fitness incorporates density dependence and a deteriorating environment along with the effect of natural selection provided by the fundamental theorem. Here, a quantitative genetic version of Fisher's model is provided, which illuminates the fundamental theorem. In particular, it has not been recognized before that the theorem treats stabilizing selection and directional selection on the underlying traits differently.